SAT0559 Malignancies in the Psoriasis Longitudinal Assessment and Registry (PSOLAR) Study: Current Status of Observations. (9th June 2015) - Fiorentino, D.; Lebwohl, M.; Ho, V.; Langley, R.; Goyal, K.; Fakharzadeh, S.; Calabro, S.; Langholff, W.
Abstract : Objectives: To report cumulative incidence and results of analysis of malignancies excluding non-melanoma skin cancers (NMSC) in PSOLAR. Methods: PSOLAR is a multicenter, longitudinal, observational study evaluating long-term safety and clinical outcomes for pts eligible to receive treatment for psoriasis with biologics and/or conventional systemic agents. The incidence of malignancies excluding NMSC (e.g.basal/squamous cell carcinomas) overall and by treatment is reported. The rules for attribution of a malignancy to a therapy use a definition of exposure based on whether pts had ever been exposed to a given therapy at any time prior to the event. In cases of exposure to >1 therapy, the rule for attribution of malignancy to a treatment is ustekinumab (UST) 1st, infliximab (IFX)/golimumab (GLM) 2nd, other biologics 3rd (nearly all adalimumab [ADA] or etanercept [ETN]), or non-biologic therapy 4th, which is consistent with the pre-specified analytic plan. Analysis using Cox hazard regression was used to identify predictors of malignancy and included medication exposure defined as UST vs no biologic and biologics other than UST (primarily ADA, IFX and ETN) vs no biologic. Results: PSOLAR is fully enrolled and, as of Aug 23, 2013, has 31 818 total pt-years of follow up with 12 095 pts. Cumulative rates of malignancy overall and across treatments were: overall 0.68 events/100 pt years of observation (PY) [95%CI: 0.59, 0.77; 215/31818], UST 0.51/100 PY [95% CI: 0.37, 0.68; 45/8870 PY], IFX/GLM (almost exclusively IFX) 0.64/100 PY [95% CI:0.42, 0.93; 27/4205, other biologics (almost exclusively ETN/ADA) 0.74/100 PY [95% CI: 0.60, 0.91; 98/13167], and non-biologic therapy 0.81/100 PY [95% CI:0.59, 1.08;45/5576]. Multivariate analysis, based on any time exposure, revealed that increasing age (p<0.001), and previous malignancy history (p<0.001) were significant predictors of malignancy. Non-white ethnicity was associated with a lower risk of malignancy (p=0.012). No statistically significant increased risk of malignancy with the use of any biologics was observed. Conclusions: Overall cumulative rates of malignancies are comparable across treatments. Age and previous malignancy were found to be associated, however, no biologics or immunomodulators were found to be associated with an increased risk of malignancy. Disclosure of Interest: D. Fiorentino Grant/research support from: Janssen Scientific Affairs, LLC, M. Lebwohl Grant/research support from: Janssen Scientific Affairs, LLC, V. Ho Grant/research support from: Janssen Scientific Affairs, LLC, R. Langley Grant/research support from: Janssen Scientific Affairs, LLC, K. Goyal Employee of: Janssen Scientific Affairs, LLC, S. Fakharzadeh Employee of: Janssen Scientific Affairs, LLC, S. Calabro Employee of: Janssen Scientific Affairs, LLC, W. Langholff Employee of: Janssen Scientific Affairs, LLC